IMPLEMENTASI IP V 6 MULTICAST DALAM JARINGAN WIRELESS - Dessyanto Boedi Prasetyo (Telematika, 2012)
Teleconferencing is a media technology to create a long-distance communication of audio data and video can also be data. With teleconferencing you can perform a communication with another person that much with a relatively low cost. At this time the use of computers in a network more complex. Some time ago has developed a new network protocol, the IPv6 is a solution to overcome the deficiencies found on previous generation protocol is IPv4Multicast is a communication mechanism of one-to-many, or point-to-multipoint. In IPv6 technology, multicast is a basic feature and has become the standard specification of every router. In the implementation is done using IPv6 multicast teleconferencing application on the LAN network topology. At the teleconference has been observed with the amount of traffic parameters that occurred during the last teleconference. Used in this study SDR and RAT teleconferencing applications. SDR (Session Directory Tool) and RAT (Robust Audio Tool) used for teleconferencing, which is part of the MBone tools. Protocol MLD (Multicast Listener Directory) is also used in this study for multicast signaling can run well.